Life review with older women: an intervention to reduce depression and improve autobiographical memory - Gonçalves, Daniela C. (2009)
Background and aims: As life expectancy rises worldwide and the population grows older, psychopathology in older adults becomes a significant public health concern and intervention methods acquire renewed importance. The aim of the present study was to assess the efficacy of Life Review as an intervention strategy in working with older women with depressive symptoms, specifically through promotion of the specificity of autobiographical memories. Methods: Twenty-two participants were randomly assigned to experimental or control conditions. Intervention consisted of four individual sessions of Life Review, structured along 14 questions aimed at prompting autobiographical memory specificity. Participants in the control condition did not receive intervention. Results: Results indicated a significant change in the experimental group, appearing as the reduction of depressive symptoms (t(20)=3.58, p<0.05) and an increase in life satisfaction (t(20)=-3.83, p<0.05), as well as a significant increase in the specificity (t(20)=-3.46, p<0.05) and positivity (t(20)=-4.23, p<0.05) of autobiographical memories. All variables reached high effect sizes, with an effect size of r=0.64 regarding depressive symptoms. Conclusions: Results suggest that Life Review is a valuable tool for use with older adults, and that promotion of specific autobiographical memories is a mechanism through which the strategy attains its effectiveness